Colonization with the commensal fungus Candida albicans perturbs the gut-brain axis through dysregulation of endocannabinoid signaling. (November 2020) - Markey, Laura; Hooper, Andrew; Melon, Laverne C.; Baglot, Samantha; Hill, Matthew N.; Maguire, Jamie; Kumamoto, Carol A.
Graphical abstract: Highlights: C. albicans GI colonization increases anxiety-like behavior and basal serum CORT. Treatment with FAAH inhibitor URB597 reversed both behavior and CORT phenotypes. C. albicans altered lipid and endocannabinoid levels in the brain and GI tract. Changes in hepatic gene expression reflected increased lipids measured in GI tract. Abstract: Anxiety disorders are the most prevalent mental health disorder worldwide, with a lifetime prevalence of 5–7 % of the human population. Although the etiology of anxiety disorders is incompletely understood, one aspect of host health that affects anxiety disorders is the gut-brain axis. Adolescence is a key developmental window in which stress and anxiety disorders are a major health concern. We used adolescent female mice in a gastrointestinal (GI) colonization model to demonstrate that the commensal fungus Candida albicans affects host health via the gut-brain axis. In mice, bacterial members of the gut microbiota can influence the host gut-brain axis, affecting anxiety-like behavior and the hypothalamus-pituitary-adrenal (HPA) axis which produces the stress hormone corticosterone (CORT). Here we showed that mice colonized with C. albicans demonstrated increased anxiety-like behavior and increased basal production of CORT as well as dysregulation of CORT production following acute stress. The HPA axis and anxiety-like behavior are negatively regulated by the endocannabinoid N-arachidonoylethanolamide (AEA). We demonstrated that C. albicans -colonized mice exhibited changes in the endocannabinoidome. Further, increasing AEA levels using the well-characterized fatty acid amide hydrolase (FAAH) inhibitor URB597 was sufficient to reverse both neuroendocrine phenotypes in C. albicans -colonized mice. Thus, a commensal fungus that is a common colonizer of humans had widespread effects on the physiology of its host. To our knowledge, this is the first report of microbial manipulation of the endocannabinoid (eCB) system that resulted in neuroendocrine changes contributing to anxiety-like behavior.